2015
DOI: 10.1039/c5ra07851b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the carbon nanotube surface modification on the microstructure of thermoplastic binders

Abstract: The structural properties of polymer nanocomposites based on thermoplastic polyimides filled with the surface-modified carbon nanotubes (CNT) have been studied by means of the fully-atomistic molecular-dynamics simulations. The influence of a distibution of functional carboxyl groups over the CNT surface on the polymer-matrix density distribution, and the orientational ordering of polymer chains have been investigated. It was shown that the polymer shifts far away from the nanoparticle surface with increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 72 publications
3
39
0
Order By: Relevance
“…The system included about 1296 chains of length N = 32 (degree of polymerization n = 8). For bringing together results of dissipative particle dynamics and molecular dynamics simulation, we set n = 8. We studied the melt of polyimide, that is, the volume fraction of the polymer was set as φ = 1.…”
Section: Methods and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The system included about 1296 chains of length N = 32 (degree of polymerization n = 8). For bringing together results of dissipative particle dynamics and molecular dynamics simulation, we set n = 8. We studied the melt of polyimide, that is, the volume fraction of the polymer was set as φ = 1.…”
Section: Methods and Modelmentioning
confidence: 99%
“…A recent investigation of nanocomposites structures based on R‐BAPB and R‐BAPS polyimides filled with CNT or graphene allowed one to determine the origin of different crystallization behavior of these polyimides. Using atomistic molecular dynamics, it was found that in the nanocomposites, R‐BAPB chains form an ordered structure near the surface of CNT or grapheme . which could be associated with an initial stage of crystallization induced by nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…At present, we are not aware of any studies regarding the simulation of CNC‐reinforced PLA composites. Our choice of the simulation methodology relies on the atomistic simulation of modified CNC in various environments as well as on the experience gained in the area of atomistic simulation of nanocomposites …”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…In recent years, much research effort has been focused on the synthesis and characterization of advanced polymer composites containing functional nanofillers. A wide range of polymers, from thermally stable heterocyclic polymers in films and in bulk to polymer hydrogels, has been the subject of investigations in the context of being matrices for nanocomposite formation …”
Section: Introductionmentioning
confidence: 99%